The relationship between maternal motivation for children's dental care and the incidence of caries in children aged 7-9 years in SDN 37 Sungai Bangek: Hubungan motivasi ibu terhadap perawatan gigi anak dengan kejadian karies anak 7-9 tahun di SDN 37 Sungai Bangek - Mahata, Intan Batura Endo; Yandi, Satria; Sitorus, Ayu Andira; Ningrum, Valendriyani; Ferdina, Resa (Makassar Dental Journal, 2024)
Factors that influence motivation are age, education, occupation, environment and economy. The most motivation comes from parents, especially mothers, as the closest person to the child's role to accompany, provide motivation and education related to oral health maintenance in children. This study discusses the relationship between maternal motivation for dental care for child-ren aged 7-9 years with the incidence of caries at SDN 37 Sungai Bangek. Quantitative research of analytical survey type with cross-sectional design was conducted in December 2023 with a sample size of 79 people by simple random sampling. Data were collected from the results of questionnaires and dental caries examinations, univariate analysis was presented in the form of frequency distribution and percentage, bivariate analysis using the chi-square test, and processed with the SPSS v.26.0 pro-gramme. The results showed that most mothers' motivation was weak as much as 64.5%, most dental caries status was very high as much as 32.9%, and there was a relationship between maternal motivation towards dental care for the children with the inci-dence of caries (p=0.003). It was concluded that there was a relationship between maternal motivation towards dental care for child-ren aged 7-9 years with the incidence of caries at SDN 37 Sungai Bangek with a weak motivation category and very high caries.